2011
DOI: 10.1103/physreva.83.053402
|View full text |Cite
|
Sign up to set email alerts
|

Electron-positron pair creation induced by quantum-mechanical tunneling

Abstract: We study the creation of electron-positron pairs from the vacuum induced by two spatially displaced static electric fields. The strength and spatial width of each localized field is less than required for pair-creation. If, however, the separation between the fields is less than the quantum mechanical tunneling length associated with the corresponding quantum scattering system, the system produces a steady flux of electron-positron pairs. We compute the time-dependence of the pair-creation probability by solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…In these cases, the underlying (Dirac or Klein-Fock-Gordon) equation simplifies to an ordinary differential equation (allowing for a WKB approach, for example, see also [30][31][32][33][34]). However, to the best of our knowledge, there are no analytic non-perturbative results for fields E(t, x) which genuinely depend on space x and time t. So far, this case has only been treated numerically via the Wigner formalism (see, e.g., [35][36][37]) or a direct integration of the Dirac equation (see, e.g., [38][39][40]). This lack of understanding is not only unsatisfactory from a theoretical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the underlying (Dirac or Klein-Fock-Gordon) equation simplifies to an ordinary differential equation (allowing for a WKB approach, for example, see also [30][31][32][33][34]). However, to the best of our knowledge, there are no analytic non-perturbative results for fields E(t, x) which genuinely depend on space x and time t. So far, this case has only been treated numerically via the Wigner formalism (see, e.g., [35][36][37]) or a direct integration of the Dirac equation (see, e.g., [38][39][40]). This lack of understanding is not only unsatisfactory from a theoretical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that by following this approach the required field strength can be reduced by three orders of magnitude. Most recently another proposal sug gested the use of multiple fields but without direct crossing [22]. In this case quantum tunneling can trig ger the pair creation even though the field is subcriti cal.…”
Section: Introductionmentioning
confidence: 99%
“…Since Sauter [2] and Schwinger [3] obtained the pair creation rate in a static field, many theoretical and experimental studies on this topic have been performed [4][5][6][7][8][9]. It has also been shown that the pair creation rate can be improved by tailoring the applied field [10][11][12][13]. However, the pair birth process itself, such as the space and momentum correlations between the just-created electrons and positrons, is less studied [6,14,15].…”
mentioning
confidence: 99%